Adsorption Properties of Lac Dyes on Wool, Silk, and Nylon - Bo Wei; Qiu-Yuan Chen; Guoqiang Chen; Ren-Cheng Tang; Jun Zhang (Journal of Chemistry)
There has been growing interest in the dyeing of textiles with natural dyes. The research about the adsorption properties of natural dyes can help to understand their adsorption mechanism and to control their dyeing process. This study is concerned with the kinetics and isotherms of adsorption of lac dyes on wool, silk, and nylon fibers. It was found that the adsorption kinetics of lac dyes on the three fibers followed the pseudosecond-order kinetic model, and the adsorption rate of lac dyes was the fastest for silk and the slowest for wool. The activation energies for the adsorption process on wool, silk, and nylon were found to be 107.15, 87.85, and 45.31 kJ/mol, respectively. The adsorption of lac dyes on the three fibers followed the Langmuir mechanism, indicating that the electrostatic interactions between lac dyes and those fibers occurred. The saturation values for lac adsorption on the three fibers decreased in the order of wool > silk > nylon; the Langmuir affinity constant of lac adsorption on nylon was much higher than those on wool and silk.